Pengaruh Penerapan Green Accounting, Ukuran Perusahaan dan Environmental Social and Governance (ESG) Terhadap Nilai Perusahaan Pada Perusahaan yang Terindeks IDX ESG Leader - Azifa Ababil; Nurma Gupita Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study to prove green accounting, company size and ESG on corporate value in compani included in the IDX ESG Leader. This research employs a quantitative method utilizing documentary data in the form of secondary data. The sample of the study consisted of 12 companies using a purposive sampling technique. The data analysis employed descriptive statistical tests, classical assumption tests and multiple linear regression analysis. The test results indicate that green accounting, company size and ESG have a negative but insignificant effect on firm value in companies indexed in IDX ESG Leader. This finding indicates that companies listed in the IDX ESG Leaders index generally have consistent corporate value due to their strong sustainability reputation, leading investors to tend to give positive assessments to entities perceived as trustworthy. Furthermore, the research findings also identified that a companys value is more influenced by overall market perception than by differences in each companys sustainability practices. The implementation of this research is expected to serves as a foundational consideration for management and stakeholders in formulating strategis to enhance firm value, particularly through the more consistent application of green accounting, company size and ESG aspects as a core component of sustainability strategy.